Skylarks and Rebels : a Memoir about the Soviet Russian Occupation of Latvia, Life in a Totalitarian State, and Freedom. - Laima, Rita (Ibidem Press, 2017)
Skylarks and Rebels is a story about the fate of Latvia in the 20th century as told by Rita Laima. Laima, a Latvian-American, chose to leave behind the comforts of life in America to explore the land of her ancestors, which in the 1980s languished behind the Iron Curtain. In writing about her own experiences in a totalitarian state, Soviet-occupied Latvia, Laima delves into her family's past to understand what happened to her fatherland and its people during and after World War II. She also pays tribute to some of Latvia's remarkable people of integrity who risked their lives to oppose the brutal and destructive Soviet state.